Emotional Dynamics: Grieving Experiences of Women After Abortion - Ekklesia, Petra; Salsabila, Raina; Putri, Sofia Tri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study explores the complex emotional dynamics and grieving process experienced by a woman following an induced abortion, utilizing Kübler-Ross’s five-stage grief model (denial, anger, bargaining, depression, acceptance) as a theoretical framework. A qualitative narrative approach was employed, with data collected through an in-depth, semi-structured online interview with a 20-year-old participant who underwent an abortion at age 18. Non-participant observation of non-verbal cues supplemented the interview data. Thematic analysis was conducted to map the subject’s experiences onto the stages of grief. Findings confirm that the participant navigated all five stages of grief, though in a non-linear and highly individual sequence. The depression stage was notably prolonged, while the eventual movement toward acceptance was significantly facilitated by entering a new, supportive romantic relationship, which provided a crucial "safe space." The experience was compounded by feelings of isolation, stigmatization, and a lack of adequate social support from her partner at the time of the procedure. The study underscores that abortion, particularly under stressful conditions, constitutes a significant psychological loss that can trigger a profound grieving process. Recommendations include integrating psychosocial education into reproductive health programs and conducting further comparative research on the experiences following legal versus illegal procedures. Keywords: abortion, grief, Kübler-Ross, qualitative research, psychological impact